Two Polyurethane Adhesives for PVDF Fixation Show Superior Biocompatibility in a Rat Model. Issue 1 (2nd January 2022) - Heise, Daniel; Mirlas, Yelyzaveta; Helmedag, Marius; Eickhoff, Roman; Kroh, Andreas; Lambertz, Andreas; Klink, Christian Daniel; Neumann, Ulf Peter; Klinge, Uwe; Tolba, Rene
Abstract: Background: The current standard for open and laparoscopic repair of incisional hernia consist of an abdominal wall augmentation by mesh implantation. However, the ideal fixation method of the prothesis material remains under discussion, due to potential complications of conventional fixation methods such as chronic abdominal pain or intestinal obstruction. As the use of adhesive based mesh fixation is an option of growing interest, the aim of this experimental study was to investigate the strength and biocompatibility of two newly developed polyurethane-based adhesives in comparison to a cyanoacrylatic adhesive, which is currently in clinical use. Methods: Two experimental polyurethane/urea-based adhesives (Adhesive-A and Adhesive-B) were compared to a conventional cyanoacrylatic adhesive and an untreated control group. Biomechanical testing was carried out using a pull-out test in uniaxial tensile mode, while biocompatibility assessment was performed in a rat model with 40 Sprague-Dawley rats receiving a subcutaneous implanted PVDF mesh fixed by the corresponding adhesive. Histological and immunohistochemical analysis by a Tissue FAXS system examined the tissue integration of the mesh/adhesive combination and characterized the foreign body reaction. Results: Biomechanical testing of the mesh/adhesive combinations showed a minimal strength of 15.08 N without a significant difference between the groups. Cellular penetration into the mesh/adhesive interface was significantly improved after application of polyurethane adhesives and Adhesive-A showed a significantly lower migration of CD68 positive cells to the adhesive sites compared to cyanoacrylate after 7 days. Conclusion: The developed polyurethane-based adhesives are a promising alternative with sufficient adhesive strength and superior short-term biocompatibility to cyanoacrylate.